Integration of Environmental, Social, and Governance (ESG) Factors into Target Costing in Lean Production Systems: A Systematic Literature Review - Ralfsamy, Achmad Daffa; Ruwary, Cinda Nongfasya; Alfarizi, Ikhsan; Ramadhan, M. Faalih Athoullah; Yusnaini, Yusnaini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This systematic literature review critically challenges the reductionist paradigm of traditional Lean Production, arguing that its narrow focus on physical waste elimination often termed "Green Lean" is inadequate for addressing complex, modern Environmental, Social, and Governance (ESG) mandates. To prevent the operational risks of greenwashing and false sustainability, manufacturing systems must undergo a holistic transformation that inherently integrates social accountability and governance transparency. By synthesizing 20 high-quality articles published between 2020 and 2026 using the PRISMA methodology, this study formulates an integrative framework that explicitly positions Target Costing as a crucial financial mediator within the Lean ecosystem. The research argues that the implementation of "Green Target Costing" effectively translates qualitative ESG compliance metrics into rigorous, quantifiable cost parameters during the pre-production design phase. Consequently, this strict cost control mechanism forces entities to internalize social and environmental investments rather than treating them as mere externalities. Furthermore, the study strongly advocates for socio-technical integration, demonstrating that digital systems and Big Data act as essential facilitators to successfully align Lean's operational agility with ethical stakeholder expectations without compromising human well-being. Ultimately, this research definitively debunks the prevailing myth that sustainability initiatives inherently stifle economic efficiency. The findings assert that integrating ESG dimensions into target cost structures is not merely an ethical obligation, but an absolute strategic imperative to ensure long-term competitive resilience in the face of rigorous global market disruptions.